1997
DOI: 10.1074/jbc.272.38.23481
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase CβII Activation by 1-β-d-Arabinofuranosylcytosine Is Antagonistic to Stimulation of Apoptosis and Bcl-2α Down-regulation

Abstract: 1-␤-D-Arabinofuranosylcytosine (ara-C. ara-C also causes apoptosis in HL-60 cells which can be mimicked by exogenous ceramide. However, the signaling role for ara-C-induced diacylglycerol (DAG) is not defined. We found that Bcl-2 levels were increased by treatment of HL-60 cells with exogenous DAG or 12-O-tetradecanoylphorbol-13-acetate (TPA). In contrast, exogenous ceramide treatment caused a decrease in cellular Bcl-2 levels. Thus, ara-C stimulates the synthesis of two second messengers with opposing effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…In agreement with this hypothesis, we and others have found that pharmacologic agents which directly inhibit PKC (eg staurosporine), 99a down-regulate PKC upon chronic exposure (eg bryostatin 1), or ablate PKC expression (eg PKC antisense oligonucleotides) have all been shown to enhance the lethal actions of Ara-C. 93,95,100 Interestingly, in the latter study, ceramide exposure decreased whereas diglyceride exposure increased expression of the anti-apoptotic protein Bcl-2 in leukemic cells. 97,100 More recently, bryostatin 1 and the PKC inhibitor safingol have been shown to block Ara-Cmediated MAP kinase activation in association with potentiation of leukemic cell apoptosis, effects which have found to be mimicked by the MEK1 inhibitor PD98059. 92,93,101 Bryostatin 1 and PD98059 have also been found to promote taxolinduced apoptosis in leukemic cells.…”
Section: The Potential Roles Of Protein Kinase C and Map Kinase Signasupporting
confidence: 78%
“…In agreement with this hypothesis, we and others have found that pharmacologic agents which directly inhibit PKC (eg staurosporine), 99a down-regulate PKC upon chronic exposure (eg bryostatin 1), or ablate PKC expression (eg PKC antisense oligonucleotides) have all been shown to enhance the lethal actions of Ara-C. 93,95,100 Interestingly, in the latter study, ceramide exposure decreased whereas diglyceride exposure increased expression of the anti-apoptotic protein Bcl-2 in leukemic cells. 97,100 More recently, bryostatin 1 and the PKC inhibitor safingol have been shown to block Ara-Cmediated MAP kinase activation in association with potentiation of leukemic cell apoptosis, effects which have found to be mimicked by the MEK1 inhibitor PD98059. 92,93,101 Bryostatin 1 and PD98059 have also been found to promote taxolinduced apoptosis in leukemic cells.…”
Section: The Potential Roles Of Protein Kinase C and Map Kinase Signasupporting
confidence: 78%
“…PDBu is a reagent known to be a tumor promoter capable of stimulating cell proliferation through PKC activation (Mochly-Rosen and Kauvar, 1998). Although the role of PKC in apoptosis is not consistent in the literature (Lavin et al, 1996;Deacon et al, 1997), the bulk of evidence suggests that PKC, especially PKC␣, activated by phorbol esters such as phorbol 12-myristate 13-acetate and PDBu, inhibits apoptosis (Lavin et al, 1996;Deacon et al, 1997;Whitman et al, 1997;Mochly-Rosen and Kauvar, 1998). In the case of PKCinduced apoptosis, there is evidence suggesting that down-regulation rather than DAG activation of PKC is responsible for this effect, because prolonged exposure to a stable phorbol ester form could result in downregulation of PKC expression (Leszczynski, 1996;Deacon et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…To date, dierent genes including Bcl-2 family members, caspases, and other signaling pathways have been implicated in apoptosis (Cory, 1995;Korsmeyer, 1995). Several reports indicate that dierent PKCs are also involved in apoptotic signaling pathways (Barr et al, 1997;Berra et al, 1997;Datta et al, 1997;DiazMeco et al, 1996;Emoto et al, 1995Emoto et al, , 1996Ghayur et al, 1996;Mizuno et al, 1997;Whelan and Parker, 1998;Whitman et al, 1997). When U937 cells were exposed to ionizing radiation, TNF-a or anti-Fas antibody, cells underwent apoptosis (Emoto et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that activation of nPKCs by protease cleavage may allow these PKC isoenzymes to exert pro-apoptotic eects. In contrast, PKC-bII was demonstrated to be critical in antagonizing Ara-Cinduced apoptosis in the HL-60 acute myelogenous leukemia line (Whitman et al, 1997) and in inhibiting c-myc-induced apoptosis of small cell lung cancer cells (Barr et al, 1997).…”
Section: Introductionmentioning
confidence: 99%